Central hypertension is a non‐negligible cardiovascular risk factor - Cheng, Yi‐Bang; Li, Yan; Cheng, Hao‐Min; Siddique, Saulat; Huynh, Minh Van; Sukonthasarn, Apichard; Chen, Chen‐Huan; Wang, Ji‐Guang (The journal of clinical hypertension (Greenwich, Conn.), 2022)
High blood pressure (BP) confers cardiovascular risk. However, the clinical value of central BP remains debatable. In this article, we aim to briefly review the prognosis, diagnosis, and treatment of central hypertension. Central and brachial BPs are closely correlated. In most prospective investigations, elevated central and peripheral BPs were similarly associated with adverse outcomes. Outcome‐driven thresholds of the central systolic BP estimated by the type I device were on average 10 mmHg lower than their brachial counterparts. Cross‐classification based on the central and brachial BPs identified that nearly 10% of patients had discrepancy in their status of central and brachial hypertension. Irrespective of the brachial BP status, central hypertension was associated with increased cardiovascular risk, highlighting the importance of central BP assessment in the management of hypertensive patients. Newer antihypertensive agents, such as renin–angiotensin–aldosterone system inhibitors and calcium channel blockers, were more efficacious than older agents in central BP reduction. Clinical trials are warranted to demonstrate whether controlling central hypertension with an optimized antihypertensive drug treatment will be beneficial beyond the control of brachial hypertension.